HOW DOES WOMEN IN SECURING ELECTORAL VOTE IN INDONESIAN POLITIC? INSIGHT FROM SOUTH SUMATERA PROVINCE - Harahap, Raegen; Mujiburrahman (International Journal of Research -GRANTHAALAYAH, 2024)
The issue of women's representation in politics has become an interesting discourse in various countries, even in Indonesia. The advancement of female candidates needs to be appreciated in the midst of the patriarchal culture that is still inherent in Indonesia. The presence of women in politics cannot be separated from the role of family ties. This is the focus and purpose of this article, which is to describe the family ties that influence women's electability in politics. The research method used in this article is a qualitative-descriptive method through literature study to explain the family ties factor in Ratu Tenny Leriva's representation as a senator for the 2024 South Sumatra Electoral District. Using the theoretical framework of the Richter model of family ties, this study reveals that Ratu Tenny Leriva's election cannot be separated from Herman Deru's position and influence. As a former Governor, Regent, and Chairman of the Regional Representative Council of the NasDem Party in South Sumatra, Herman Deru facilitated Ratu Tenny Leriva in building a positive image, popularity, and electability, despite being a new-comer and still 23 years old. This can be seen from Ratu Tenny Leriva's involvement in various public spaces and campaign periods, where many billboards or posters include Herman Deru's photo. This family bond is an important factor and political modality in Ratu Tenny Leriva's electability in South Sumatra in 2024.